Intelligent Scheduling-Driven Co-Creation Manufacturing Closed-Loop Reform Oriented by Industry-Education Integration - Wang, Tao; Yuan, Yumeng; Cheng, Mingyuan; Yang, Fan; Tan, Haojian (Education Insights, 2026)
In the context of multidisciplinary integration, universities must bridge the gap between classroom teaching and industrial practice to achieve deep industry-education integration. Currently, university teaching faces issues such as misalignment of curriculum with industry needs and low efficiency in resource allocation. This paper proposes a closed-loop teaching reform model oriented by industry-education integration, built upon an intelligent course scheduling system for academic resources and a university-enterprise co-creation manufacturing platform. Through AI-driven smart scheduling to optimize on-campus course and resource allocation, and by introducing real enterprise projects into the teaching process, a closed-loop flow from classroom to practice and back is established. We detail the closed-loop teaching process and system architecture, which enable data-driven teaching optimization and collaborative innovation between universities and enterprises. This approach provides a new idea for talent training reform under a multidisciplinary background.